Proceedings. 7th International Workshop on Principles of Software Evolution, 2004.
DOI: 10.1109/iwpse.2004.1334781
|View full text |Cite
|
Sign up to set email alerts
|

Managing evolving requirements in an outsourcing context: an industrial experience report

Abstract: In this paper we discuss several difficulties managing evolving requirements by means of an industrial case study conducted at LogicaCMG. We report on setting up a requirements management system in an outsourcing context and its application in real-life. The experience results in several lessons learned, questions to be answered in the future on how to manage evolving requirements, and solution directions. We propose a conceptual framework of a requirements engineering system tailored for outsourcing environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 4 publications
3
20
0
Order By: Relevance
“…According to Von Knethen, defining a workable traceability model is a neglected activity in many approaches. Our earlier research confirms the importance of defining a traceability model (Lormans et al 2004). Some initial experiments concerned a static traceability model.…”
Section: Document Standards Templates and Reference Modelssupporting
confidence: 80%
See 2 more Smart Citations
“…According to Von Knethen, defining a workable traceability model is a neglected activity in many approaches. Our earlier research confirms the importance of defining a traceability model (Lormans et al 2004). Some initial experiments concerned a static traceability model.…”
Section: Document Standards Templates and Reference Modelssupporting
confidence: 80%
“…For managing the requirements in this particular case, LogicaCMG was forced to make separate requirements documents in which the traceability was manually set by the requirements engineers. Some of the mechanisms used for managing requirements evolution in this setting are described in our earlier work dealing with the same case study (Lormans et al 2004).…”
Section: Case Study Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Lormans et al [9] conducted an industrial case study with a single international company to understand how requirements traceability is impacted by the outsourcing context. The authors specified requirements for a requirements management system in the context of inter-organizational development.…”
Section: Related Workmentioning
confidence: 99%
“…Further, various researchers recognized that inter-organizational specifics need to be carefully considered when applying requirements traceability in the outsourcing context. Beside the small case study on requirements traceability within an international company by Lormans et al [9], there are no empirical studies that examined the specific challenges of leverage requirements traceability in inter-organizational projects. To close this gap in this relevant area of software development, we found that a systematic study of this problem is necessary.…”
Section: Related Workmentioning
confidence: 99%